Interactive effect between Selenium and Vitamin C levels on risk of hypertension among adult women in the United States: evidence from NHANES 2011 to 2020 - Wu, Dongfang; Fan, Ping; Ching, Sze Wan (Frontiers in Nutrition, 2025)
BackgroundHypertension poses an imperative global health risk, affecting over 1 billion people and contributing to cardiovascular disease, especially for women. While previous studies suggest micronutrients such as Vitamin C or Selenium can help reduce blood pressure, research on their interactive effects remains limited.MethodsThis cross-sectional study analyzed data from 9,343 women aged 20 years and older in NHANES (2011–2020). Logistic regression analysis was conducted to evaluate the effect of each micronutrient on hypertension. To account for potential interactions between micronutrients, we calculated the relative excess risk due to interaction, which assessed their combined effect on hypertension.ResultsWe confirmed the individual associations of Vitamin C and Selenium with hypertension, showing significant negative correlations (p < 0.05). Participants were then divided into four groups, and those with high intakes of both Vitamin C and Selenium had a significantly lower risk of hypertension (p < 0.05), supporting the association between the combined intake of these nutrients and lower hypertension risk, though no synergistic effect was observed.ConclusionThe findings support the combined intake of Vitamin C and Selenium in hypertension prevention, broadening thoughts on the level of nutrition for the treatment of hypertension. These results suggest a potential association between adequate supplementation of Vitamin C and Selenium and lower blood pressure. However, further rigorous clinical studies are essential to validate and strengthen these findings.